2000
DOI: 10.1097/00006231-200001000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes mellitus on regional cerebral glucose metabolism and regional cerebral blood flow

Abstract: Previous studies have shown both increased and decreased regional cerebral glucose metabolism-blood flow (rMRGlu-rCBF) values in diabetes. We sought to elucidate the influence of diabetes on rMRGlu-rCBF in 57 patients with pure cerebral microangiopathy. Sixteen of 57 patients had diabetes requiring therapy (11 NIDDM, 5 IDDM). Using a special head-holder for exact repositioning, rMRGlu (PET) and rCBF (SPET) were imaged and measured in slices, followed by MRI. White matter and cortex were defined within regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 43 publications
0
31
1
1
Order By: Relevance
“…Some studies did not have similar gender distributions between T2DM and non-diabetic control groups, but female subjects had higher CBF than male subjects (Pirson, Vander Borght, and Van Laere 2006; Gur and Gur 1990), which may obscure the CBF difference between the groups. Some studies also did not account for brain volume difference, which has been shown to largely explain reduced CBF (Sabri et al 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Some studies did not have similar gender distributions between T2DM and non-diabetic control groups, but female subjects had higher CBF than male subjects (Pirson, Vander Borght, and Van Laere 2006; Gur and Gur 1990), which may obscure the CBF difference between the groups. Some studies also did not account for brain volume difference, which has been shown to largely explain reduced CBF (Sabri et al 2000). …”
Section: Discussionmentioning
confidence: 99%
“…If such a biomarker can be developed, future study could focus on identifying interventions that can prevent the appearance or slow the progression of white matter microstructural changes in patients with diabetes. Over the last 10 years, investigators have used a variety of imaging techniques, including MRI, single photon emission computed tomography (30,31), and positron emission tomography (32), to determine whether structural abnormalities could be identified in the brains of patients with (36), and decreased cerebral gray matter density (37,38) in type 1 diabetic subjects. Some of these structural abnormalities have corresponded to age of diabetes onset (35), A1C levels, hypoglycemia (37), and the presence of retinopathy (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to link T2D to alterations in CBF, but with mixed results. Initial studies using single photon emission computed tomography found a reduction in CBF in patients with T2D relative to control participants 38,39 . Later studies with larger sample sizes have had difficulty identifying consistent patterns of CBF change in individuals with T2D.…”
Section: Functional Imaging Studiesmentioning
confidence: 99%